THE CONTRIBUTION OF THE SERAMBI INDONESIA AND WASPADA NEWSPAPERS IN IMPLEMENTATION OF THE ISLAMIC LAW IN ACEH - Darmadi, Darmadi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: This study investigates the role of media in implementing Islamic law and overcoming aqîdah trivialization in Aceh, which focuses on the contribution of Serambi Indonesia and Waspada newspapers. The results show that, the two newspapers play important roles in socializing Qanun as regulations on Islamic law; reporting Qanun socialization from Islamic law institution; publishing news on the implementation and supervision of the Islamic law, providing some comments from the leaders regarding the implementation of the Islamic law to prevent aqîdah trivialization. Constraints faced by the Media in reporting the issues of sharia implementation and shallowing faith of the ummah include terror and intimidation; a must to conceal the identity of the under-age; and the difficulty of confirming and clarifying with informants/perpetrators.Keywords: mass media, Islamic sharia, aqidah, deviant sects